The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0144598717741039
|View full text |Cite
|
Sign up to set email alerts
|

Paleogeomorphological reconstruction and geological implications of the weathered-crust karst on the top of the Middle Triassic Leikoupo Formation in the Longgang area, Sichuan Basin, China

Abstract: Weathered-crust karst carbonate is developed in the third submember of the fourth member of the Middle Triassic Leikoupo Formation (Lei 4 3 submember) in the Longgang area of Sichuan Basin, China, and acts as an important oil and gas reservoir. To reconstruct the paleogeomorphology of the weathered-crust karst, we analyzed the seismic thickness of the interval from the erosional unconformity surface on the top of the Leikoupo Formation to the karst at the bottom of the third member of the Xujiahe Formation (Xu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The pressure evolution during the middle Permian is divided into three stages: (1) a brief overpressure stage (T 2 -T 3 ); (2) an overpressure stage (J 1 -K 2 ); and (3) an overpressure reduction stage (K 2 -present). Liu et al (2018a) reconstruct the Middle Triassic 3D paleogeomorphology of weathered karst in the Longgang area, Sichuan Basin. They identify three geomorphological units above the Leikoupo Formation, referred to as the karst highlands, karst transitional zone, and karst basin.…”
Section: Formation Of Natural Gas Reservoirs In the Sichuan Basinmentioning
confidence: 99%
“…The pressure evolution during the middle Permian is divided into three stages: (1) a brief overpressure stage (T 2 -T 3 ); (2) an overpressure stage (J 1 -K 2 ); and (3) an overpressure reduction stage (K 2 -present). Liu et al (2018a) reconstruct the Middle Triassic 3D paleogeomorphology of weathered karst in the Longgang area, Sichuan Basin. They identify three geomorphological units above the Leikoupo Formation, referred to as the karst highlands, karst transitional zone, and karst basin.…”
Section: Formation Of Natural Gas Reservoirs In the Sichuan Basinmentioning
confidence: 99%
“…The development of numerous karst reservoirs is usually based on long-term tectonic uplift and strong denudation. In contrast, the Dongwu movement was a short-term tectonic uplift, with a duration of about 0.5–2.5 Ma . Several studies revealed that the residual thickness of the Maokou Formation in the Sichuan Basin varies from 180 to 360 m, and the maximum eroded thickness does not exceed 200 m .…”
Section: Introductionmentioning
confidence: 99%